The basis of submission (to/of) authority - Al-Ahmed, Mohammed Sulaiman; Ahmed, Luqman Othman; Amin, Mohammed Nasih Mohammed (Journal of Legal and Political Studies, 2023)
The research deals with two important issues, namely: the basis of individuals' submission to authority, and the basis of authority's submission to the general will of individuals. The basis of submission in both cases lies in natural law, because the submission of individuals to public authority stems from the premise and logic of the social contract under which they gave up part of their freedoms in exchange for living in an organized and safe entity that guarantees them the realization of their interests and the protection of their rights. However, this restriction represented by the individuals’ submission to authority must be in light of what is required by the rules of justice, otherwise the individuals have the right violate the orders that violate the principles of justice, i.e. violating the principles of natural law, and this is what makes the authority subject to the same law to ensure that individuals obey its orders voluntarily. The research presented an analysis and a derivation of the basis of submission in both cases, and this is what lead the researchers to adopt the notion behind the dual title.
Keywords: individuals submission to authority; natural law; social contract; rules of justice; restriction